Entrepreneurship a Misguided Quest: A Higher Education Review - Ssemugenyi, Fred; Obsiye, Fuad A (World Journal of Vocational Education and Training, 2022)
Following a successful integration of entrepreneurship into the content-based curricula and the eventual significant growth of Asian economy, Uganda, through its universities joined the movement. The intention was to boost Uganda’s economy to a level of generating sufficient jobs, increased incomes, and improved goods and services. While this is a truism, the effectiveness of this intervention is still undergoing empirical testing. This study delved into the effectiveness of this strategy while using Kampala International University (KIU) and Nkumba University (NKU) as study samples. Utilizing a mixed-method explanatory sequential design, numerical data were collected first from 74 undergraduates, followed by interviews with 10 key informants. Results indicated that teaching methods significantly and positively affected students’ intended learning outcomes (ILOs) in entrepreneurship since the p. value (≤ 0.001) was below the margin of error (0.05) which was the minimum level of probability required in this study to declare statistical significance. But of the three parameters of X, the lecture method did not statistically impact the achievement of ILOs (Sig value = 0.489 > 0.05). In addition, although the interview responses recognised the importance of a balanced entrepreneurship curriculum in predicting students’ ILOs, the numerical data did not indicate any statistical significance (adjusted r2 = 0.254). Lastly, teacher quality as part of the predictor variables had a positive and significant impact on the achievement of ILOs in entrepreneurship (adjusted r2 0.452), but of the three sub-variables of teacher quality, content mastery and professionalism had a weak impact (Sig. 0.148 > 0.05 & Sig. 0.093 > 0.05).